Analisis Proses Kreatif Mendesain Lukisan "Diskusi" Alvian Anta Putra - Aegis Rabbani, Radian; Fadhlurrohman, Moch Farhan (Magenta | Official Journal STMK Trisakti, 2024)
When we look at a painting, we certainly think that what has been examined contains elements of aesthetic and symbolic value involving a structured understanding of creative thinking. For the painter, it requires several creative processes in painting a work of art so that it can be created into a highly valuable masterpiece. The painting 'Discussion' was created in 2017. In the painting, figures of people with emoticons on their faces are seen holding phones, which, when associated with today's society, prioritize their phones over the surrounding environment. The issue under study began with the author's interest in an owner of a painting by a well-known young artist. The author was particularly intrigued when research revealed that the painting won an annual painting competition, 'The Most Promising Emerging Artist UOB Painting of the Year 2017.' The author then decided to make it the object of a research study. Behind the painting that is equivalent to such a competition, there is undoubtedly a creative process to design it. The data collection technique involves observation. The research method uses descriptive qualitative research. This study aims to analyze the creative process of creating the painting 'Discussion' using Choudary's 2019 theory, consisting of five stages of the creative design process: Empathize, Define, Ideate, Prototype, Test. The results of this analysis hope to yield new findings that can be discovered through research on the creative process of designing paintings. This research is expected to provide new insights for artists or readers who enjoy designing paintings